ChemInform Abstract: Microwave Assisted Palladium‐Catalyzed Synthesis of Phthalazinones and Pyridopyridazinones. Issue 42 (1st October 2013) - Rao, K. Penta; Basak, Ashok K.; Deb, Prasant K.; Sharma, Somesh; Reddy, L. Krishnakanth
Abstract from o‐bromobenzaldehydes, arylhydrazines, and Mo(CO)6 as a non‐toxic alternative for CO